Sequential development of human fetal pancreatic islets of langerhans cells: A histopathological study - Banerjee, Smita Singh; Arole, Vasanti (Asian Journal of Medical Sciences, 2018)
Background: Knowledge of normal development pattern of various endocrine cells of the human pancreas is of paramount importance, due to its implication during replacement therapies in the treatment of diabetes mellitus. Development related literature of fetal pancreas is scanty due to ethical and technical difficulties to obtain fetuses. Aims and Objectives:Present study was conducted on 49 fetuses from gestational weeks 10 to 40 to obtain the sequential appearance and arrangement of islets of langerhans cells of pancreas. Material and Methods: Forty nine fetuses were collected in formal saline immediately after abortion, medical termination of pregnancy or premature delivery. The fetal pancreas was processed for paraffin blocks. Sections were taken and stained with Haematoxylin and Eosin as well as Gomori’s modified Aldehyde Fuchsin stain and observed under light microscope. Results: Islets were initially a small number of cells with Alpha cells, which were seen at 10th week of gestation. Beta cells were identified in the islets of fetuses around 16 weeks of gestation. Delta cells were observed from 17 weeks onwards and islets appeared as a group from the beginning of 19th week. Conclusion: In the present study we observed a sequential development of Alpha, Beta and Delta cells and subsequent grouping of the islets. The exact gestational time of appearance of above islet cells and their encapsulation can add to the existing knowledge data base for successful transplant of pancreas in patients of insulin dependent diabetes mellitus. Asian Journal of Medical Sciences Vol.9(5) 2018 67-72